Mulheres brasileiras: relações de classe, de “raça” e de gênero no mundo do trabalho - Helena Hirata (Confins)
This article presents the convergences and main differences between the women's situation in Brazil and in France. To compare these specific realities, the article analyses the sexual division of domestic and professional work in the two countries and the relation between family and professional life. It compares also the different modalities of social and work precariousness and their unequal consequences on Brazilian and French women.